PEMIKIRAN AL-GHAZALI TENTANG PENDIDIKAN DAN RELEVANSINYA DENGAN PENDIDIKAN KONTEMPORER - Basit, Marwan Abdul (Universitas Islam Syekh-Yusuf, 2022)
The figure of Al-Ghazali has had such a great effect both in the history of Islamic thought and on the religiosity of the Muslims. Al-Ghazali was not only known as a theologian, but he also mastered the fields of jurisprudence (law), ethics, logic, and even philosophical studies. He is considered an encyclopedic Islamic scientist by mastering almost all scientific treasures from various very different disciplines. Al-Ghazali's thoughts were not only limited to matters of the religious sciences, but he was also famous for his thoughts in the field of education. This study uses a qualitative approach with the type of library research or called literature study with a study of documentation in the form of several literatures and archives that are used as data samples by researchers as instruments in research. The results of this study reveal the influence of Al-Ghazali's thoughts in the field of education which currently still exists and is a reference for Muslims, especially among Sunni adherents. Al-Ghazali's thoughts in the field of education include; namely aspects of the role of education, educational goals, educational curriculum, educational methods, teacher ethics, and student ethics. Keywords: Al-Ghazali Thought, Education, end Contemporary Education